Rethinking of phosphodiesterase 5 inhibition: the old, the new and the perspective in human health - Paronetto, Maria Paola; Crescioli, Clara (Frontiers in Endocrinology, 2024)
The phosphodiesterases type 5 (PDE5) are catalytic enzymes converting the second messenger cyclic guanosine monophosphate (cGMP) to 5' GMP. While intracellular cGMP reduction is associated with several detrimental effects, cGMP stabilization associates with numerous benefits. The PDE5 specific inhibitors, PDE5i, found their explosive fortune as first-line treatment for erectile dysfunction (ED), due to their powerful vasoactive properties. The favorable effect for ED emerged as side-effect when PDE5i were originally proposed for coronary artery disease (CAD). From that point on, the use of PDE5i captured the attention of researchers, clinicians, and companies. Indeed, PDE5-induced intracellular cGMP stabilization offers a range of therapeutic opportunities associated not only with vasoactive effects, but also with immune regulatory/anti-inflammatory actions. Chronic inflammation is acknowledged as the common link underlying most non-communicable diseases, including metabolic and cardiac diseases, autoimmune and neurodegenerative disorders, cancer. In this scenario, the clinical exploitation of PDE5i is undeniably beyond ED, representing a potential therapeutic tool in several human diseases. This review aims to overview the biological actions exerted by PDE5i, focusing on their ability as modulators of inflammation-related human diseases, with particular attention to inflammatory-related disorders, like cardiac diseases and cancer.